Scale-up modes: Profiling activity configurations in scaling strategies. Issue 6 (December 2021) - Piaskowska, Dorota; Tippmann, Esther; Monaghan, Sinéad
Abstract: Scale-ups, or scaling firms, provide an important contribution to the economy. However, there is little understanding of the characteristics of their scaling strategies, compared to the high-growth strategies of start-ups and mature firms. To address this, we build on the Penrosean view of firm growth and the literature on high-growth firms to identify the critical growth-enabling activities of scaling firms with digital business models: financing, innovation, digitization, and acquisitions. Using cluster analysis of a sample of 184 Unicorn and emerging Unicorn scale-ups with digital business models, we identify four distinct activity configurations, or scale-up modes: network growers, focused scalers, organic innovators, and constricted scalers. We discuss the theoretical implications for the literature on scaling firms, Penrose's theory of firm growth in the digitization era, and firm growth research more generally.